CRITICAL DISCOURSE ANALYSIS IN THE ANTHOLOGY PERJAMUAN KHONG GUAN BY JOKO PINURBO - Faiz, Alfidiya; Seli, Sesilia; Saman, Sisilya (Universitas Tanjungpura, 2025)
This study aims to examine critical discourse analysis in Joko Pinurbo